Fatty acid-based methacrylate polymers as viscosity modifiers for mineral oils. Issue 3 (19th July 2018) - Lomège, Juliette; Negrell, Claire; Robin, Jean-Jacques; Lapinte, Vincent; Caillol, Sylvain
Abstract : In this work, partially biobased methacrylate polymers with various fatty acid side chains were used as efficient polymeric viscosity modifiers for mineral paraffinic oil (MPO). Firstly, oleic, palmitic, myristic and lauric acids were functionalized with 2-hydroxyethyl methacrylate by Steglich esterification to provide suitable monomers for radical polymerization. The resulting monomer from oleic acid (2-(methacryloyloxy)ethyl oleate) was polymerized through conventional radical polymerizations and telomerization in order to evaluate the influence of the polymer molecular weight on its efficiency as a viscosity modifier. Additionally, methacrylate monomers containing different chain lengths of fatty acids were involved in reversible addition–fragmentation chain transfer polymerization to obtain polymers with similar molecular weights in order to compare their efficiency as viscosity modifiers. For this purpose, all fatty acid-based polymers were mixed at 3 wt.% in MPO and relative viscosity measurement between MPO and polymer–MPO blends was performed at various temperatures. The results demonstrated that fatty acid-based methacrylate polymers have a higher polymer contribution on MPO viscosity with increasing temperature. This specific viscosimetric behavior was related to the coil polymer chains' expansion with temperature, which was improved by increasing the polymer molar mass and the length of dangling fatty alkyl chains hanging off polymer backbones.